2021
DOI: 10.3390/healthcare9111539
|View full text |Cite
|
Sign up to set email alerts
|

Defining Potentially Inappropriate Prescriptions for Hypoglycaemic Agents to Improve Computerised Decision Support: A Study Protocol

Abstract: In France, around 5% of the general population are taking drug treatments for diabetes mellitus (mainly type 2 diabetes mellitus, T2DM). Although the management of T2DM has become more complex, most of these patients are managed by their general practitioner and not a diabetologist for their antidiabetics treatments; this increases the risk of potentially inappropriate prescriptions (PIPs) of hypoglycaemic agents (HAs). Inappropriate prescribing can be assessed by approaches that are implicit (expert judgement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Not performed or not included in the clinical records could likewise lead to inappropriate prescribing. Validated criteria to assess inappropriate prescriptions in T2DM have not been developed so far [ 29 ]; however, criteria used in this study are quite consistent with those used elsewhere. Since there is no clear information on adherence, prescribing does not mean taking the medication; in addition, several drugs, when associated with lack of control, may be a risk marker more than a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Not performed or not included in the clinical records could likewise lead to inappropriate prescribing. Validated criteria to assess inappropriate prescriptions in T2DM have not been developed so far [ 29 ]; however, criteria used in this study are quite consistent with those used elsewhere. Since there is no clear information on adherence, prescribing does not mean taking the medication; in addition, several drugs, when associated with lack of control, may be a risk marker more than a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Future challenges will concern the collective use of CDSS by several healthcare professionals such as nurses, general practitioners and clinical pharmacists to promote larger multidisciplinary approaches thanks to CDSS. The present work is part of a larger, multidisciplinary research project on inappropriate prescriptions in patients with diabetes; one of the next steps will be the development of antidiabetic drug rules for inclusion in the CDSS, and its implementation in primary care 41 …”
Section: Discussionmentioning
confidence: 99%
“…Constant re-assessment of the rules is also important for ensuring specificity and avoiding spurious alerts and alert fatigue 15,40. These rules can evolve through multidisciplinary collaboration work based on systematic reviews, qualitative studies and validation by consensus 41. This approach might help to extend the CDSS's field of competence to: (i) drugs not currently detected; (ii) more specific patient profiles; and (iii) different contexts.…”
mentioning
confidence: 99%
“…A method for developing explicit definitions of PIPADs in patients with T2DM has been published previously [ 23 ]. The present systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our present results highlight the need to establish an expert consensus on PIPAD definitions that can be translated explicitly (via a qualitative study and a Delphi survey) and applied to patients with T2DM. Next to the systematic review, the qualitative study will aim to identify as PLOS ONE many explicit definitions as possible, then the Delphi survey will aim to provide a consensus among them as show as in our published protocol [23]. Most strategies for prescribing ADs are based on guidelines and expert's opinion with implicit definitions.…”
Section: The Value Of Explicit Definitionsmentioning
confidence: 99%